A COMPREHENSIVE UNDERSTANDING OF MAJJAVAHA SROTODUSHTI NIDANA - R, *Aswathi.; M, Chetan. (International Journal of Ayurveda and Pharma Research, 2016)
The concept of Srotas has explained diligently by our Acharyas to understand the functioning of our body. Charaka brings out the terms like Sira, Dhamani, Srotas under one heading and defines these are the structures which are Avakashayukta and carry the bodily elements and if they are intact and functioning properly, the body will be free from diseases. Hence we can say Srotas is a broad term which is essential for transportation of vital elements of the body. Srotas are innumerable in number as there are innumerable number of Bhava in the body and the concept of Srotomaya Purusha is told. The things which are carried through the Srotas will undergo transformation as it reaches its destination. Srotas are classified for our basic understanding into Bahya (Sthula) and Abhyantara (Sukshma). While explaining the Abhyantara srotas, Charaka has enumerated Majjavahasrotas, its Dushti nidana and Lakshana. Susrutha on the other hand has not included Majjavaha srotas and he has not described a structure to carry Majja in the body, rather he believed Majja is the entity present inside the Asthi. Majja is always proved to be controversial as the term Masthishka Majja/Mastulunga is a coined term along. This paper will explain about the conceptual understanding of Majjavaha Srotodushti Nidana and a precise understanding of Majja and Mastulunga.